PENGARUH WORKING CAPITAL TURNOVER (WCTO) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN ON ASSET (ROA) PADA PT MARTINA BERTO TBK PERIODE 2014-2023 - Emelia Fauzi, Shifa; Prasetyo, Hendri (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Working Capital Turnover and Total Asset Turnover on Return on Assets. The method used in this research is a quantitative approach with a descriptive nature. The source of this research is secondary data. The population of this study is the entire annual financial statements of PT Martina Berto Tbk, and the sampling technique used is purposive sampling over a period of 10 years. The data analysis method in this study uses classical assumption tests, multiple linear regression tests, hypothesis tests, and the coefficient of determination using SPSS 25.The results of this study indicate that, partially, Working Capital Turnover has a negative effect on Return on Assets at PT Martina Berto Tbk for the period 2014-2023. This is evident from the significance value < 0.05 (0.012 < 0.05) and the t-count < t-table (-3.350 < 2.306). Partially, the Total Asset Turnover variable has a positive and significant effect on Return on Assets, as seen from the significance value < 0.05 (0.001 < 0.05) and the t-count > t-table (6.283 > 2.306). Simultaneously, there is a significant effect between Working Capital Turnover and Total Asset Turnover on Return on Assets, as seen from the significance value < 0.05 (0.001 < 0.05) and the F-count > F-table (20.771 > 4.737).